Plutarque. Editions, traductions, paratextes - Françoise Frazier (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2017)
This book brings together twelve papers by members of the Réseau Thématique européen "Plutarque" regarding Plutarch in the Humanistic Age. It is organized into three parts : the first one focuses on the translations, the second one is devoted to the philological work and shows how humanistic conjectures and exegesis are still valuable for modern editors; finally, the third one adresses the reinterpretation and reuse of Plutarch's work.Such a volume is aimed both at the Plutarchists - they either deal with textual criticism or with Plutarch's recep-tion - and at the specialists of the Renaissance. It may be of interest also for anyone concerned by translatology or by the legacy of Antiquity and its importance in modern times.